Strengthening Selfhood of Islamic Boarding School Students through Value-Based Psychoeducation - Andika Ari Saputra; M. Zainal Arifin; Umar Alfaruq A. Hasyim; Muslihati Muslihati; IM Hambali; Ahmad Yusuf Sobri; Adefta Prasenja; Muhammad Alfian Ma'arif (Jurnal Medika: Medika, 2025)
Adolescent Islamic students studying in Islamic boarding schools (pesantren) face complex challenges in developing their selfhood amidst the influence of digital culture and modern social pressures. The mismatch between the religious values taught in Islamic boarding schools and the realities of life outside the school leads some students to experience a selfhood crisis, weak emotional regulation, and a decline in spiritual awareness. This community service program aims to design and implement a psychoeducational program based on Islamic values derived from the Quran and reflective practices (such as muhasabah and tadabbur) to strengthen selfhood. Using the Service Learning (SL) method and a participatory approach, this activity is implemented in the form of training, reflective discussions, and psychoeducational services. Results indicate an increase in students' selfhood, self-awareness, emotional regulation skills, and self-confidence in facing the dynamics of modern life without losing Islamic spiritual values. This program demonstrates its effectiveness as a psychoeducational model for strengthening selfhood, incorporating Islamic values that are relevant and contextual to the needs of today's Islamic boarding school youth.